2006
DOI: 10.1099/mic.0.29177-0
|View full text |Cite
|
Sign up to set email alerts
|

The arl locus positively regulates Staphylococcus aureus type 5 capsule via an mgrA-dependent pathway

Abstract: Most clinical Staphylococcus aureus strains produce either type 5 or type 8 capsular polysaccharides. The production of these capsules is influenced by various environmental factors. To study the regulation of capsule, Tn551 transposon mutagenesis and transcriptional reporter gene fusion were employed to identify several putative regulatory loci that influenced capsule gene expression. One of these, the arl locus, was chosen for further analysis. Tn551 was found to insert within the coding region (near the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 35 publications
3
80
2
Order By: Relevance
“…Although capsule production is very important in the survival of S. aureus during different phases of infection, very little is known about the mechanism that regulates the cap operon. Several global regulators have been shown to affect the production of the capsule, indicating that several environmental and host signals must be integrated to fine-tune this process (Luong et al, , 2003(Luong et al, , 2011Luong & Lee, 2006;Chen et al, 2007;Dassy et al, 1993;Gupta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although capsule production is very important in the survival of S. aureus during different phases of infection, very little is known about the mechanism that regulates the cap operon. Several global regulators have been shown to affect the production of the capsule, indicating that several environmental and host signals must be integrated to fine-tune this process (Luong et al, , 2003(Luong et al, , 2011Luong & Lee, 2006;Chen et al, 2007;Dassy et al, 1993;Gupta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several global regulators have been shown to control the production of the capsule, including agr, sarA, arl and mgrA, as well as others (Luong et al, , 2003(Luong et al, , 2011Luong & Lee, 2006;Chen et al, 2007;Dassy et al, 1993;Gupta et al, 2013). A detailed analysis of the cap operon promoter has revealed that it is highly regulated (Ouyang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We checked that the agrA mutant showed a phenotype similar to that of the agrCA mutant. The DNA fragment of apsR or agrA amplified with specific primers was cloned into pCL15, an E. coli-S. aureus shuttle vector with a Pspac promoter (Luong & Lee, 2006). The plasmid was electroporated into RN4220.…”
Section: Methodsmentioning
confidence: 99%
“…The transposon was transduced to Newman and 10833 using phage 80 as described by Kasatiya & Baldwin (1967). For complementation of the mutation, aur from 10833 or Newman was cloned into the IPTGinducible vector pCL15 (Luong & Lee, 2006). Primers aur-pCL15Fwd (59-GTGAGGAAATTTTCAAGATATG-39) and aur-pCL15Rev (59-TTACTCCACGCCTACTTCATTCC-39) were used to amplify the aur gene from 10833 or Newman genomic DNA.…”
Section: Methodsmentioning
confidence: 99%